Respuesta :
Option B.
Given that the equation 7x − 8y = 6 is multiplied by 1 and it is added to the first equation the new equation is
7x - 8y + x + 3y = 5 + 6; equivalent to
8x -5y =11; and the system is that equation with the second original one.
7x- 8y = 6
Given that the equation 7x − 8y = 6 is multiplied by 1 and it is added to the first equation the new equation is
7x - 8y + x + 3y = 5 + 6; equivalent to
8x -5y =11; and the system is that equation with the second original one.
7x- 8y = 6
Answer:
B : show that the solution to the system of equations 8x - 5y = 11 and 7x - 8y = 6 is the same as the solution to the given system of equations
Step-by-step explanation:
I just took the test and got it right